2016
DOI: 10.1002/pros.23277
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib Trial of Cabazitaxel and Tasquinimod in Men With Heavily Pretreated Metastatic Castration Resistant Prostate Cancer (mCRPC): The CATCH Trial

Abstract: We determined the RP2D of tasquinimod combined with cabazitaxel to be 0.5 mg daily following a 3 week lead-in of tasquinimod 0.25 mg with growth factor support. No unexpected toxicities occurred. Prostate 77: 385-395, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Cabazitaxel is also being studied with a small-molecule inhibitor tasquinimod in the Phase I CATCH trial. 27 Tasquinimod limits the activity of myeloid-derived suppressor cells (MDSCs), which accumulate in the tumor microenvironment and inhibit the antitumor activity of T, natural killer, and dendritic cells. The small molecule binds to protein S100A8/A9 and interrupts the positive feedback of further MDSC recruitment.…”
Section: Treatment Sequencingmentioning
confidence: 99%
“…Cabazitaxel is also being studied with a small-molecule inhibitor tasquinimod in the Phase I CATCH trial. 27 Tasquinimod limits the activity of myeloid-derived suppressor cells (MDSCs), which accumulate in the tumor microenvironment and inhibit the antitumor activity of T, natural killer, and dendritic cells. The small molecule binds to protein S100A8/A9 and interrupts the positive feedback of further MDSC recruitment.…”
Section: Treatment Sequencingmentioning
confidence: 99%
“… 25 The results from this study have provided a rationale for clinical testing of a tasquinimod combination with chemotherapy in CRPC patients. As cabazitaxel in combination with prednisone has emerged as a standard chemotherapy in the post-docetaxel setting, 53 , 54 the CATCH prostate cancer trial (NCT01513733) 55 has been initiated where a combination of tasquinimod and cabazitaxel is being tested in metastatic CRPC after progression on docetaxel (see below).…”
Section: Combination Strategies With Tasquinimod In Crpcmentioning
confidence: 99%
“… 56 By combining the results of these studies showing improved antitumor response in prostate cancer with combination of tasquinimod and androgen ablation or radiation therapy, it is conceivable that these combinations may be a successful therapeutic approach which warrants further testing. 25 , 55 …”
Section: Combination Strategies With Tasquinimod In Crpcmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase Ib trial CATCH (NCT01513733) assessed the safety and activity of tasquinimod plus cabazitaxel versus cabazitaxel monotherapy in 25 patients with pretreated Completed phase III clinical trials with immunotherapeutic treatments for genitourinary malignancies Petrylak et al [155] Lenalidomide + docetaxel + prednisone vs. docetaxel + prednisone mCRPC (first-line) mCRPC, metastatic castration-resistant prostate cancer; mRCC, metastatic renal cell carcinoma; OS, overall survival; RT, radiotherapy.mCRPC[161]. The preliminary results of this study indicated a more than 30% PSA decrease in 63% of patients (95% CI: 41-81) and a median composite PFS of 8.5 months (95% CI: 4.2-16.4).…”
mentioning
confidence: 99%